Carbon dioxide mineralized solid waste foam geopolymer and forming method thereof

By activating the slag powder and combining the combination of a variety of solid waste powders, high-strength earth polymers are formed, and the thermal insulation performance and CO2 mineralization reaction are optimized through foam preparation technology, the shortcomings of solid waste utilization and foam earth polymer preparation in the existing technology are solved, and efficient carbon sequestration and resource utilization are achieved.

CN119797820APending Publication Date: 2025-04-11ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411769258.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has shortcomings in solid waste utilization and foam polymer preparation, including low activity of silicon-aluminum components in solid waste, resulting in insufficient material strength, and failure to systematically optimize the foam generation and distribution process, which limits the lightweight, thermal insulation performance and CO2 mineralization efficiency of the material.

Method used

By activating the slag powder, the solubilization of the silicon-aluminum component can be improved, and the activity of the silicon-aluminum component is stimulated in an alkaline environment, forming a high-strength polymer. At the same time, foam preparation technology is used to uniformly mix the foam with solid waste-based slurry to optimize thermal insulation performance and CO2 mineralization reaction.

Benefits of technology

The preparation of high-strength earth polymers has been achieved, which significantly improves the activity of solid waste, the insulation performance of materials and the CO2 mineralization efficiency, reduces carbon emissions, meets the requirements of low-carbon environmental protection, and has significant environmental and economic benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a carbon dioxide mineralized solid waste foam geopolymer and a forming method thereof, and relates to the technical field of inorganic cementing materials. The carbon dioxide mineralized solid waste foam geopolymer is prepared from the following raw material components in parts by weight: 90 to 110 parts of compound solid waste powder, 40 to 60 parts of water glass, 10 to 20 parts of sodium hydroxide, 20 to 40 parts of water and 20 to 30 parts of foam. According to the preparation method, the dissolubility of silicon and aluminum components in the slag powder is improved by activating the slag powder, the activity of the slag powder is effectively excited in an alkaline environment by combining the characteristics of the materials such as the steel slag and the metakaolin, a high-strength geopolymer is formed, and foam and solid waste-based slurry are uniformly mixed through a foam preparation technology; the heat insulation performance of the material is optimized, the density is reduced, carbon dioxide is solidified in the form of carbonate through CO2 gas carbonization treatment and mineralization reaction in the material, the carbon sequestration capacity of the material is enhanced, and efficient recycling of industrial waste is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic gelling materials, in particular to a carbon dioxide mineralized solid waste foam geopolymer and a molding method thereof. Background Art

[0002] As the global climate change problem becomes increasingly serious, reducing carbon emissions and recycling solid waste resources have become the focus of the international community. Due to its high carbon emissions and large resource consumption, the cement and concrete industry urgently needs to transform towards a "green and low-carbon" direction. At the same time, the efficient utilization of bulk industrial solid waste has also become a key area of ​​green development. In recent years, carbon capture and utilization (CCU) technology has received widespread attention. Among them, carbon dioxide mineralized solid waste foam geopolymer, as a new type of green material, has become a research hotspot because of its solid waste utilization and carbon emission reduction functions. It not only achieves carbon emission reduction by mineralizing CO2 and fixing it in the foam geopolymer matrix, but also effectively utilizes industrial solid waste, reducing resource consumption and environmental burden.

[0003] As a low-carbon and environmentally friendly inorganic cementitious material, geopolymer has excellent properties such as high strength, fire resistance, and corrosion resistance, and has gradually become an alternative to traditional silicate cement. The three-dimensional network structure formed by alkali-activated silica-alumina materials gives geopolymer good mechanical and thermal stability. The introduction of foam brings significant advantages to the material. Foam not only greatly reduces the density of the material, making the geopolymer lightweight and easy to transport and construct, but also improves its thermal insulation performance, making it suitable for scenes that require lightweight thermal insulation materials.

[0004] In addition, the porous structure of the foam provides more channels for the diffusion and mineralization reaction of CO2, making it easier for carbon dioxide to diffuse in the geopolymer matrix and react with the material to form carbonate minerals, thereby enhancing the strength and durability of the material. The foam can also increase the surface area of ​​the material, further promoting the absorption and fixation efficiency of CO2. This CO2 mineralization achieved through the foam structure not only reduces carbon emissions, but also effectively improves the resource utilization rate of solid waste. Therefore, the advantages of foam geopolymer in light weight, heat insulation, CO2 diffusion and mineralization make it one of the important technologies to promote the green and low-carbon transformation of the cement concrete industry.

[0005] However, the existing technology has the following shortcomings in the utilization of solid waste and the preparation of foamed geopolymers: First, solid waste contains a large amount of silicon and aluminum components, which can theoretically be used to manufacture geopolymer materials. However, due to the low activity of silicon and aluminum components, it is difficult to fully stimulate and utilize them, resulting in insufficient strength of the prepared geopolymer materials and the inability to fully realize the potential value of solid waste. Secondly, the preparation process and method of foamed geopolymers still need to be further studied. Current technology has not yet been able to systematically optimize the generation and distribution process of foams, limiting the role of foams in material lightweighting, thermal insulation performance, and CO2 mineralization efficiency. Therefore, improving the activity of solid waste and optimizing the preparation process of foamed geopolymers are technical problems that need to be solved urgently in this field. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] In order to overcome the deficiencies of the prior art, the present invention provides a carbon dioxide mineralized solid waste foam geopolymer with high carbon fixation capacity and a molding method thereof.

[0008] (II) Technical solution

[0009] The technical solution adopted by the present invention to solve the technical problem is:

[0010] A carbon dioxide mineralized solid waste foam geopolymer comprises the following raw material components in parts by weight: 90-110 parts of compound solid waste powder, 40-60 parts of water glass, 10-20 parts of sodium hydroxide, 20-40 parts of water, and 20-30 parts of foam.

[0011] Preferably, the composite solid waste powder includes components such as steel slag, slag, and kaolin, and the composite solid waste powder is obtained by mixing, grinding, and sieving 90-110 parts of activated slag raw material, 10-20 parts of steel slag, and 10-20 parts of kaolin.

[0012] Preferably, the activated slag raw material is obtained by adding 10-20 parts of sodium hydroxide to 100 parts of slag raw materials after crushing, grinding, screening and washing, and then performing microwave drying and smelting for 1-2 hours.

[0013] Preferably, the foam is formed by pressing air into a spray pot containing a surfactant solution through a compressor, and the spray pot mixes the compressed gas with the surfactant solution and releases the foamed body by spraying, thereby forming foam.

[0014] Preferably, a carbon dioxide mineralized solid waste foam geopolymer and a molding method thereof include the following steps:

[0015] Step 1. crushing, grinding, screening and washing the slag raw materials to obtain an original slurry;

[0016] Step 2. adding sodium hydroxide to the original slurry to obtain a mixed solution A, wherein the mass ratio of the slag to the sodium hydroxide is 1:0.1-0.2;

[0017] Step 3. After stirring and aging the mixed solution A for 10-12 hours, the mixed solution is dried using a microwave device, and then activated for 20-40 minutes after drying to obtain a mixed solution B;

[0018] Step 4. Smelting the mixture B at 600-800° C. for 2-3 hours, crushing, grinding and sieving after cooling to obtain an activated slag raw material;

[0019] Step 5. The activated slag raw material, steel slag and metakaolin obtained in step 4 are mixed in a ratio of 1:0.1-0.2:0.1-0.2:, ground and sieved to obtain a composite solid waste powder;

[0020] Step 6. Mix the composite solid waste powder obtained in step 5 with water glass, sodium hydroxide, and water in a ratio of 1:0.4-0.6:0.1-0.2:0.2-0.4, and stir with a stirrer at a speed of 500 r / min for 3-5 minutes to obtain a solid waste-based polymer gelling material slurry;

[0021] Step 7. The solid waste-based polymer gelling material slurry obtained in step 6 is mixed with the pre-prepared foam in a ratio of 1:0.05-0.10, and agitated at a speed of 1000 r / min for 2 minutes using a stirrer to fully mix the foam and the slurry to obtain a solid waste-based foamed polymer gelling material slurry;

[0022] Step 8. Pour the solid waste-based foam geopolymer gelling material slurry obtained in step 7 into a silicone mold, use a vibrator to slightly vibrate the mold to eliminate large volume voids, let it stand at room temperature for 24 hours, and demold to obtain a solid waste-based foam geopolymer specimen;

[0023] Step 9. Place the solid waste-based foamed geopolymer specimen obtained in step 8 into a carbonization reactor, evacuate with a vacuum pump until the digital pressure gauge displays negative 0.85-0.9 MPa and maintain for 15-20 seconds, reset the digital pressure gauge to zero and use the air pressure at this time as the zero point, then inject CO2 gas and accurately control the air pressure through a pressure reducing valve, keeping the digital pressure gauge at 0.10-0.3 MPa, and carbonize in this environment for 40-48 hours before taking out to obtain the finished solid waste-based foamed geopolymer specimen.

[0024] Preferably, the sodium hydroxide in step 2 is of analytical grade and has an effective ingredient content greater than 96%, and the output power of the microwave equipment in step 3 is 5-6 W / g.

[0025] Preferably, the metakaolin is calcined at 750-900°C and has a particle size of 0.1-100 μm, and the slag is S95 grade slag with a particle size of 0.1-100 μm and a specific surface area of ​​400-500 m 2 / kg.

[0026] Preferably, the water glass has a modulus of 2.0-3.3, a solid content of 30-50%, and a Baume degree Be' / 25°C of 40-50.

[0027] Preferably, the sodium hydroxide in step 6 is of chemically pure grade, and the content of active ingredients is greater than 90%.

[0028] Preferably, the ratio of water, sodium dodecyl sulfate and xanthan gum in the surfactant for preparing the foam in step 7 is 1000:0.005-0.010:0.001-0.002, the sodium dodecyl sulfate is of analytical grade with an active ingredient content greater than 92.5%, and the xanthan gum is of USP grade.

[0029] (III) Beneficial effects

[0030] The present invention provides a carbon dioxide mineralized solid waste foam geopolymer and a molding method thereof. It has the following beneficial effects:

[0031] 1. The present invention provides a carbon dioxide mineralized solid waste foam geopolymer and a molding method thereof. By activating the slag powder, the solubility of the silicon and aluminum components therein is improved, and the properties of materials such as steel slag and kaolin are combined to effectively stimulate their activity in an alkaline environment to form a high-strength geopolymer.

[0032] 2. The present invention provides a carbon dioxide mineralized solid waste foam geopolymer and a molding method thereof. The foam and solid waste-based slurry are evenly mixed through foam preparation technology, thereby optimizing the thermal insulation performance of the material and reducing the density. After carbonization treatment with CO2 gas, a mineralization reaction occurs inside the material, causing the carbon dioxide to solidify in the form of carbonate, thereby enhancing the carbon fixation capacity of the material and realizing efficient recycling of industrial waste.

[0033] 3. The carbon dioxide mineralized solid waste foam geopolymer and its molding method provided by the present invention not only have good mechanical strength and thermal insulation properties, but also can significantly reduce carbon emissions and meet low-carbon environmental protection requirements. The material has significant environmental and economic benefits, especially in the field of green building materials and has broad application prospects. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0035] Embodiment 1:

[0036] The embodiment of the present invention provides a carbon dioxide mineralized solid waste foam geopolymer and a molding method thereof, comprising the following steps:

[0037] Step 1. 1000 g of slag is crushed, ground, sieved and washed to obtain an original slurry;

[0038] Step 2. Add 100 g of sodium hydroxide to the original slurry, mix and stir to obtain a mixed solution A;

[0039] Step 3. The obtained mixed solution A was stirred and aged for 10 hours and then dried using a 5000W microwave device. After drying, activation was continued for 20 minutes to obtain a mixture B;

[0040] Step 4. The mixture B is smelted at 600° C. for 2 hours, and after cooling, it is crushed, ground, and sieved to obtain an activated slag raw material;

[0041] Step 5. 1000 g of activated aluminum ash slag, 100 g of steel slag, and 100 g of metakaolin are mixed, ground, and sieved to obtain a composite solid waste powder;

[0042] Step 6. 1000 g of the composite solid waste powder is mixed with 400 g of water glass, 100 g of sodium hydroxide and 200 g of water, and stirred for 3 minutes to obtain a solid waste-based polymer gelling material slurry;

[0043] Step 7. The solid waste-based polymer gelling material slurry obtained in step 6 is mixed with the pre-prepared foam in a ratio of 1:0.10, and agitated at a speed of 1000 r / min for 2 minutes using a stirrer to fully mix the foam and the slurry to obtain a solid waste-based foamed polymer gelling material slurry;

[0044] Step 8. Use a stirrer to stir at a speed of 1000 r / min for 2 minutes to fully mix the foam and the slurry to obtain a solid waste-based foam geopolymer gelling material slurry;

[0045] Step 9. Place the solid waste-based foamed geopolymer specimen obtained in step 8 into a carbonization reactor, evacuate the air with a vacuum pump until the digital pressure gauge shows negative 0.85 MPa and maintain for 15 seconds, reset the digital pressure gauge to zero and use the air pressure at this time as the zero point, then inject CO2 gas and accurately control the air pressure through a pressure reducing valve, keeping the digital pressure gauge at 0.10 MPa, and carbonize in this environment for 40 hours before taking out to obtain a solid waste-based foamed geopolymer specimen finished product a.

[0046] Embodiment 2:

[0047] The embodiment of the present invention provides a carbon dioxide mineralized solid waste foam geopolymer and a molding method thereof, comprising the following steps:

[0048] Step 1. 1000 g of slag is crushed, ground, sieved and washed to obtain an original slurry;

[0049] Step 2. Add 150 g of sodium hydroxide to the original slurry, mix and stir to obtain a mixed solution A;

[0050] Step 3. The obtained mixed solution A was stirred and aged for 11 hours and then dried using a 5000W microwave device. After drying, activation was continued for 30 minutes to obtain a mixture B;

[0051] Step 4. The mixture B is smelted at 700° C. for 2 hours, and after cooling, it is crushed, ground, and sieved to obtain an activated slag raw material;

[0052] Step 5. 1000 g of activated aluminum ash slag, 150 g of steel slag, and 150 g of metakaolin are mixed, ground, and sieved to obtain a composite solid waste powder;

[0053] Step 6. 1000 g of the composite solid waste powder is mixed with 500 g of water glass, 150 g of sodium hydroxide and 300 g of water, and stirred for 3 minutes to obtain a solid waste-based polymer gelling material slurry;

[0054] Step 7. The solid waste-based polymer gelling material slurry obtained in step 6 is mixed with the pre-prepared foam in a ratio of 1:0.075, and agitated at a speed of 1000 r / min for 2 minutes using a stirrer to fully mix the foam and the slurry to obtain a solid waste-based foamed polymer gelling material slurry;

[0055] Step 8. Use a stirrer to stir at a speed of 1000 r / min for 2 minutes to fully mix the foam and the slurry to obtain a solid waste-based foam geopolymer gelling material slurry;

[0056] Step 9. Place the solid waste-based foam geopolymer specimen obtained in step 8 into a carbonization reactor. Use a vacuum pump to evacuate until the digital pressure gauge shows negative 0.90 MPa and maintain for 20 seconds, reset the digital pressure gauge to zero and use the pressure at this time as the zero point, then inject CO2 gas and accurately control the pressure through a pressure reducing valve, keep the digital pressure gauge at 0.2 MPa, place it in this environment for carbonization for 44 hours, and then take it out to obtain a solid waste-based foam geopolymer specimen finished product b.

[0057] Embodiment 3:

[0058] The embodiment of the present invention provides a carbon dioxide mineralized solid waste foam geopolymer and a molding method thereof, comprising the following steps:

[0059] Step 1. 1000 g of slag is crushed, ground, sieved and washed to obtain an original slurry;

[0060] Step 2. Add 200 g of sodium hydroxide to the original slurry, mix and stir to obtain a mixed solution A;

[0061] Step 3. The obtained mixed solution A was stirred and aged for 10 hours and then dried using a 5000W microwave device. After drying, activation was continued for 20 minutes to obtain a mixture B;

[0062] Step 4. The mixture B is smelted at 800° C. for 3 hours, and after cooling, it is crushed, ground, and sieved to obtain an activated slag raw material;

[0063] Step 5. 1000 g of activated aluminum ash slag, 200 g of steel slag, and 100 g of metakaolin are mixed, ground, and sieved to obtain a composite solid waste powder;

[0064] Step 6. 1000 g of the composite solid waste powder is mixed with 600 g of water glass, 200 g of sodium hydroxide and 200 g of water, and stirred for 5 minutes to obtain a solid waste-based polymer gelling material slurry;

[0065] Step 7. The solid waste-based polymer gelling material slurry obtained in step 6 is mixed with the pre-prepared foam in a ratio of 1:0.05, and agitated at a speed of 1000 r / min for 2 minutes using a stirrer to fully mix the foam and the slurry to obtain a solid waste-based foamed polymer gelling material slurry;

[0066] Step 8. Use a stirrer to stir at a speed of 1000 r / min for 2 minutes to fully mix the foam and the slurry to obtain a solid waste-based foam geopolymer gelling material slurry;

[0067] Step 9. Place the solid waste-based foamed geopolymer specimen obtained in step 8 into a carbonization reactor, evacuate with a vacuum pump until the digital pressure gauge displays negative 0.9 MPa and maintain for 20 seconds, reset the digital pressure gauge to zero and use the air pressure at this time as the zero point, then inject CO2 gas and accurately control the air pressure through a pressure reducing valve, keeping the digital pressure gauge at 0.3 MPa, and carbonize in this environment for 48 hours before taking out to obtain the solid waste-based foamed geopolymer specimen finished product c.

[0068] Sample compressive strength test:

[0069] The KY-100KN universal testing machine of Shanghai Kaiyan Testing Instrument Co., Ltd. was used to test the compressive strength of the solid waste-based foam geopolymer test pieces a, b, and c. The sample size was a cylinder with a diameter and height of 50 mm. The test process was as follows:

[0070] 1) The pressure plate of the universal testing machine acts on the upper and lower surfaces of the cylindrical specimen. The test process is carried out in the force control mode and the loading speed is set to 120N / s;

[0071] 2) The test is stopped when the specimen fails, and specimen fragments about 5 mm away from the specimen surface are collected for subsequent testing;

[0072] 3) Take 5 specimens for each mix ratio, remove the discrete data exceeding 20% ​​of the average value, and calculate the valid data to obtain the average compressive strength.

[0073] The results of the compressive strength test are shown in Table 1 below;

[0074] Table 1 Sample strength

[0075] sample Strength after mineralization (MPa) Solid waste-based foam geopolymer test piece finished product a 4 Solid waste-based foam geopolymer test piece finished product b 7 Solid waste-based foam geopolymer test piece finished product c 10

[0076] By processing the slag raw materials, the alkali activation activity thereof is significantly improved. The present invention combines a compound of various solid waste powders (including steel slag, metakaolin, etc.) to further optimize the mechanical properties thereof.

[0077] Multiple examples show that different amounts of alkali activators, microwave activation time, and carbonization conditions have a significant impact on the mechanical strength and carbon fixation capacity of the final geopolymer material. Through the carbonization reaction process, carbon dioxide is solidified in the form of carbonate in the geopolymer material, which improves the environmental benefits and carbon fixation capacity of the material. The foam geopolymer material finally obtained has good thermal insulation performance and mechanical strength, realizes the efficient reuse of industrial waste, and meets the current requirements of green environmental protection.

[0078] The above specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A carbon dioxide mineralized solid waste foam geopolymer, characterized in that: The invention comprises the following raw material components in parts by weight: 90-110 parts of compound solid waste powder, 40-60 parts of water glass, 10-20 parts of sodium hydroxide, 20-40 parts of water and 20-30 parts of foam.

2. The carbon dioxide mineralized solid waste foam geopolymer according to claim 1, characterized in that: The composite solid waste powder includes components such as steel slag, slag, and kaolin, and the composite solid waste powder is obtained by mixing, grinding, and sieving 90-110 parts of activated slag raw materials, 10-20 parts of steel slag, and 10-20 parts of kaolin.

3. The carbon dioxide mineralized solid waste foam geopolymer according to claim 2, characterized in that: The activated slag raw material is obtained by adding 10-20 parts of sodium hydroxide to 100 parts of the slag raw material after crushing, grinding, screening and washing, and then performing microwave drying and smelting for 1-2 hours.

4. The carbon dioxide mineralized solid waste foam geopolymer according to claim 1, characterized in that: The foam is formed by pressing air into a spray pot filled with a surfactant solution through an air compressor, and the spray pot mixes the compressed gas with the surfactant solution and releases the foamed body by spraying, thereby forming foam.

5. A carbon dioxide mineralized solid waste foam geopolymer and a molding method thereof, characterized in that: The following steps are involved: Step 1. crushing, grinding, screening and washing the slag raw materials to obtain an original slurry; Step 2. adding sodium hydroxide to the original slurry to obtain a mixed solution A, wherein the mass ratio of the slag to the sodium hydroxide is 1:0.1-0.2; Step 3. After stirring and aging the mixed solution A for 10-12 hours, the mixed solution is dried using a microwave device, and then activated for 20-40 minutes after drying to obtain a mixed solution B; Step 4. Smelting the mixture B at 600-800° C. for 2-3 hours, crushing, grinding and sieving after cooling to obtain an activated slag raw material; Step 5. The activated slag raw material, steel slag and metakaolin obtained in step 4 are mixed in a ratio of 1:0.1-0.2:0.1-0.2:, ground and sieved to obtain a composite solid waste powder; Step 6. Mix the composite solid waste powder obtained in step 5 with water glass, sodium hydroxide, and water in a ratio of 1:0.4-0.6:0.1-0.2:0.2-0.4, and stir with a stirrer at a speed of 500 r / min for 3-5 minutes to obtain a solid waste-based polymer gelling material slurry; Step 7. The solid waste-based polymer gelling material slurry obtained in step 6 is mixed with the pre-prepared foam in a ratio of 1:0.05-0.10, and agitated at a speed of 1000 r / min for 2 minutes using a stirrer to fully mix the foam and the slurry to obtain a solid waste-based foamed polymer gelling material slurry; Step 8. Pour the solid waste-based foam geopolymer gelling material slurry obtained in step 7 into a silicone mold, use a vibrator to slightly vibrate the mold to eliminate large volume voids, let it stand at room temperature for 24 hours, and demold to obtain a solid waste-based foam geopolymer specimen; Step 9. Place the solid waste-based foamed geopolymer specimen obtained in step 8 into a carbonization reactor, evacuate with a vacuum pump until the digital pressure gauge displays negative 0.85-0.9 MPa and maintain for 15-20 seconds, reset the digital pressure gauge to zero and use the air pressure at this time as the zero point, then inject CO2 gas and accurately control the air pressure through a pressure reducing valve, keeping the digital pressure gauge at 0.10-0.3 MPa, and carbonize in this environment for 40-48 hours before taking out to obtain the finished solid waste-based foamed geopolymer specimen.

6. The carbon dioxide mineralized solid waste foam geopolymer and its forming method according to claim 5, characterized in that: The sodium hydroxide in step 2 is of analytical grade and has an effective component content greater than 96%. The output power of the microwave equipment in step 3 is 5-6 W / g.

7. The carbon dioxide mineralized solid waste foam geopolymer and its forming method according to claim 5, characterized in that: The metakaolin is calcined at 750-900°C and has a particle size of 0.1-100 microns. The slag is S95 grade slag with a particle size of 0.1-100 microns and a specific surface area of ​​400-500m 2 / kg.

8. The carbon dioxide mineralized solid waste foam geopolymer and its forming method according to claim 5, characterized in that: The water glass has a modulus of 2.0-3.3, a solid content of 30-50%, and a Baume degree Be' / 25°C of 40-50.

9. The carbon dioxide mineralized solid waste foam geopolymer and its forming method according to claim 5, characterized in that: In step 6, the sodium hydroxide is of chemically pure grade, and the content of effective ingredients is greater than 90%.

10. The carbon dioxide mineralized solid waste foam geopolymer and its forming method according to claim 5, characterized in that: In the step 7, the ratio of water, sodium lauryl sulfate and xanthan gum in the surfactant for preparing the foam is 1000:0.005-0.010:0.001-0.002, the sodium lauryl sulfate is analytical grade, the active ingredient content is greater than 92.5%, and the xanthan gum is USP grade.